Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Behavioral Mechanisms Prompted by Badges: The Goal-Gradient Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad (Workshop on Information Systems & Economics (WISE))

Modeling Languages for Business Models as Tools for Innovation: Towards a Theoretical Foundation - John, Thomas (Proceedings of the Americas' Conference on Information Systems (AMCIS))

Research on Electric Mobility in Germany: Monitoring a Commercial Battery Electric Vehicle Fleet - Görzen, Thomas; Kundisch, Dennis; Ottensmann, C.; Haubrock, A. (Proceedings of the European Electric Vehicle Congress (EEVC))

Towards a Simulation-based Approach for Evaluating Business Models for the Electric Vehicle Market - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis; Teetz, A.; Rose, M. (Proceedings of the European Electric Vehicle Congress (EEVC))

The Case for Modeling Consumer Choice Through an Adapted Total Cost of Ownership Approach - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena; Flake, S.; Freund, D.; Jung, H. (Proceedings of the European Electric Vehicle Congress (EEVC))

Providing aid to repressive terrorist source countries does not make the U.S. any safer - Gries, Thomas; Meierriecks, Daniel; Redlin, Margarete

Maritime Piracy: Socio-Economic, Political, and Institutional Determinants - Gries, Thomas; Redlin, Margarete

A Crook is a Crook ... But is He Still a Crook Abroad? On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

What is the Relationship Between Market Structure and Digitized Customer Experience? - Herrmann, Philipp; Rahman, Mohammad (INFORMS Annual Meeting)

Evaluation von Lerndesigns mit einem webbasierten Classroom Response System in der universitären Lehre - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Neugebauer, J.; Zoyke, A. (Proceedings of the 12. e-Learning Fachtagung Informatik)

Modeling Languages for Business Models as Tools for Innovation - A Systematic Review and Research Agenda - John, Thomas; Kundisch, Dennis (Tagung der Erich-Gutenberg-Arbeitsgemeinschaft Köln e.V.)

Ein TVO-Modell zur Bewertung elektrifizierter Fahrzeugflotten - Görzen, Thomas; Meier, Christian; Kundisch, Dennis (Proceedings der INFORMATIK 2014)

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Proceedings of the 22nd European Conference on Information Systems (ECIS))

Webbasierte Classroom Response Systeme in der Hochschullehre - eine eimpirische Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Magenheim, J.; Kundisch, Dennis; Herrmann, Philipp; Reinhardt, W. (43. dghd Jahrestagung)

Simulating Consumer Choice of Innovative Business Models for Electric Mobility - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Analyzing Risk Interaction Effects among IT Projects based on Modern Portfolio Theory - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (Tagungsband der Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Tagungsband MKWI 2014 - Multikonferenz Wirtschaftsinformatik

Communication roles in public events: a case study on Twitter communications - Mirbabaie, Milad; Ehnis, Christian; Stieglitz, Stefan; Bunker, Deborah (Information systems and global assemblages: (re)configuring actors, artefacts, organizations: IFIP WG 8.2 Working Conference on Information Systems)

How context impacts on media choice - Stieglitz, Stefan; Brockmann, Tobias; Mirbabaie, Milad (Proceedings of the 25th Australasian Conference on Information Systems)

The role of social media network participants in extreme events - Ehnis, Christian; Mirbabaie, Milad; Bunker, Deborah; Stieglitz, Stefan (Proceedings of the 25th Australasian Conference on Information Systems)

Collective action and the common enemy effect - De Jaegher, Kris; Hoyer, Britta (Defence and Peace Economics)
How is collective defence by players affected when they face a threat from an intelligent attacker rather than a natural threat? This paper analyses this question using a game-theoretic model. Facing an intelligent attacker has an effect if players move first and visibly set their defence strategies, thereby exposing any players who do not defend, and if the attacker is, moreover, not able to commit to a random attack. Depending on the parameters of the game, the presence of an intelligent attacker either increases the probability that players jointly defend (where such joint defence either does or does not constitute a utilitarian optimum), or decreases the probability that players jointly defend (even though joint defence is a utilitarian optimum).

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth-Sloane, Caren (Business Research)

Stock Market Reactions to Customer Service Outsourcing in Manufacturing Firms - Eggert, A; Böhm, E; Cramer, C (2015 AMA Winter Marketing Educators’ Conference Proceedings)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V; Münkhoff, E; Scheer, L. K (ISBM 2014 Academic Conference)

Selling value in business markets: Why a powerful idea often fails - Eggert, A; Haas, A; Terho, H; Ulaga, W; Münkhoff, E (ISBM 2014 Academic Conference)

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 43rd European Marketing Academy (EMAC) Conference)

Overcoming Roadblocks to Value-Based Selling: Aligning Organizational Support With Sales Force Activities - Terho, H; Eggert, A; Ulaga, W; Haas, A (2014 AMA Winter Marketing Educators’ Proceedings)

A Decision Support System for IT Security Incident Management - Rauchecker, Gerhard; Yasasin, Emrah; Schryen, Guido (11th International Conference on Trust, Privacy, and Security in Digital Business (TRUSTBUS))

Model-based Decision Support in Manufacturing and Service Networks - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Leena; Voß, Stefan (Business & Information Systems Engineering (BISE))

Modellbasierte Entscheidungsunterstützung in Produktions- und Service-Netzwerken - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Lena; Voß, Stefan (Wirtschaftsinformatik)

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program

The Epistemological Impact of Literature Reviews in Information Systems Research - Schryen, Guido

Design Research zur individuellen Förderung in der beruflichen Rehabilitation - Kremer, H.-Hugo; Zoyke, A. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Ordnungsversuche als Alternative zur Einleitung - Braukmann, U.; Dilger, B.; Kremer, H.-Hugo (Wirtschaftspädagogische Handlungsfelder.Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

Forschung in Innovationsarenen - Überlegungen zu einem Paradigma im Spannungsfeld von Erkenntnis und Gestaltung - Kremer, H.-Hugo (Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

Editorial zur Ausgabe 27: Berufsorientierung - Büchter, K.; Kremer, H.-Hugo; Zoyke, A. (bwp@ Berufs- und Wirtschaftspädagogik - online)

„...Lehrer sein dagegen sehr!“ - Überlegungen im Kontext einer reflexiven Professionalisierung - Kremer, H.-Hugo; Sloane, Peter F. E. (bwp@ Berufs- und Wirtschaftspädagogik - online)

‚Übergänge mit System?!‘ - Eine Betrachtung des Übergangs- und Berufsorientierungsprozesses aus der Perspektive von Jugendlichen - Eickhoff, A.; Kremer, H.-Hugo; Zoyke, A. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Den Übergang erleben: Übergangshandeln an der Fakultät für Wirtschaftswissenschaften (Wissenschaftlicher Beitrag) - Kremer, H.-Hugo; Rüschen, E. (Zeitschrift für Hochschulentwicklung)

Einleitung - Kremer, H.-Hugo; Tramm, T.; Wilbers, K. (Kaufmännische Bildung. Sondierungen zu einer vernachlässigten Sinndimension)